Owner-manager replacement: a venture capitalist decision model - Robert Cressy (Journal of Global Entrepreneurship Research, 2014)
We develop a theory of managerial replacement in which a venture capitalist monitors an investee firm run by a manager of unknown quality (Good or Bad). An informative signal St correlated with performance (value-added) is available to the VC at a cost in each period t. The problem is when to replace him if he underperforms. We derive a solution to this problem that takes the form of an optimal cutoff for each period t, namely, St+1, such that, given his track record, the manager will be replaced if and only if next period's signal falls below St+1. The probability of manager replacement is lower for managers with good track records, higher incremental values and lower VC discount rates, and is higher the higher the return to professional replacement, the cost of investment and the costs of monitoring manager performance. Replacement is also predicted to enhance company value.
Keywords: G24; G32; 650; Venture capital; Manager; Replacement; Bayesian learning; Monitoring; Patent